ALEKSANDR FAYNBERG AND ABDULLA ORIPOV:A COMPARATIVE- TYPOLOGICAL ANALYSIS OF POETIC THINKING, NATIONAL IDENTITY, AND EXISTENTIAL LAYERS - ODILOVA CHAROSXON SHAVKATJON KIZI, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION:  This  article  provides  a  comprehensive  comparative-typological,  hermeneutic,  and  structural-poetic  analysis  of  the  works  of  two  major representatives  of  20th-century  Uzbek  poetry  —  Aleksandr  Faynberg  and  Abdulla Oripov. The research examines their positions within the historical-literary context, models of poetic thinking, the transformation of the lyrical subject, the dialectics of national  and  universal  values,  imagery  systems,  and  existential-philosophical dimensions. The  scientific  novelty  of  the  study  lies  in  interpreting  Faynberg  and  Oripov within  a  unified  conceptual  framework,  defined  as  the  paradigms  of  individual-psychological  poetics  and  national-epic  poetics.  The  research  demonstrates  that although the two poets represent different aesthetic directions, their creative legacies complement each other and significantly expand the philosophical and artistic scope of Uzbek poetry.